Association between intra-operative meatal mismatch and urethrocutaneous fistula development in hypospadias repair. Issue 2 (April 2021) - D'Oro, Anthony; Chan, Yvonne Y.; Rosoklija, Ilina; Meyer, Theresa; Shannon, Rachel; Johnson, Emilie K.; Liu, Dennis B.; Gong, Edward M.; Maizels, Max; Matoka, Derek J.; Yerkes, Elizabeth B.; Lindgren, Bruce W.; et al.
Summary: Introduction: The Glans-Meatus-Shaft (GMS) Score is a pre-operative phenotypic scoring system used to assess hypospadias severity and risk for post-operative complications. The 'M' component is based on pre-operative meatal location, but meatal location sometimes changes after penile degloving, resulting in 'meatal mismatch.' Objective: To identify: 1) the incidence and clinical predictors of meatal mismatch, and 2) the association of meatal mismatch with post-operative urethrocutaneous fistula development. Study design: We performed a retrospective cohort study on patients who underwent primary hypospadias repair at a single center from 2011 to 2018. Meatal mismatch was defined as: upstaging (meatus moving more proximally after degloving), downstaging (moving more distally after degloving), or none. Covariates included: pre-degloving meatal location, chordee severity, penoscrotal anatomy, pre-operative testosterone, and number of stages for repair. To test the association between meatal mismatch and fistula development, we constructed two, nested, multivariable Cox proportional hazards regression models with and without meatal mismatch and compared them with the likelihood ratio test. A sensitivity analysis excluded patients with <6 months of follow-up. Results: Of 485 patients, 99 (20%) exhibited meatal mismatch, including 75 (15%) with upstaging and 24 (5%) patients with downstaging (Figure). Meatal mismatch was significantly associated with penoscrotal webbing, number of stages for repair, and pre-degloving meatal location, with downstaging being associated with more proximal meatal location. Over a median follow-up of 7.3 months (interquartile range 2.0–20.9), fistulae developed in 56 (12%) patients. On multivariable analysis, meatal upstaging was associated with a 3-fold increased risk of fistula development (Hazards Ratio [HR]: 3.04, 95% Confidence Interval [CI]: 1.44–6.45) compared to no mismatch. Meatal downstaging had similar risk of fistula development compared to no mismatch (HR: 0.99, 95% CI: 0.29–3.35). Multi-stage compared to single-stage repair was associated with reduced risk of fistula development (HR: 0.24, 95% CI: 0.09–0.66). The likelihood ratio test favored the model that included meatal mismatch. The sensitivity analysis showed similar findings. Discussion: Our short-term results suggest that meatal mismatch may be an important additional consideration to the GMS score as a tool to assess hypospadias severity, counsel families, and predict outcomes. Longer-term studies are needed to enhance the precision of risk stratification in hypospadias. Conclusions: Meatal mismatch occurred in 20% of patients undergoing hypospadias repair. Among this cohort, meatal upstaging was associated with a 3-fold increased risk of post-operative urethrocutaneous fistula development. Summary Figure 1 Flow diagram of cohort and major findings. Summary Figure 1 Summary Table 1 Sensitivity Analysis (restricted to patients with ≥6 months of follow-up, N=275) multivariable Cox regression models with and without meatal mismatch. Likelihood ratio test showed better fit with full model (p=0.04). Summary Table 1 Variable Base Model HR (95% CI), p-value Full Model HR (95% CI), p-value Pre-degloving Meatal Location      Glanular Referent Referent  Coronal 0.54 (0.09–3.24), p = 0.50 0.58 (0.10-3.53), p = 0.56  Distal/Midshaft 1.61 (0.38-6.91), p = 0.52 2.24 (0.50-10.03), p = 0.29  Proximal 3.33 (0.69-16.18), p = 0.14 7.18 (1.21-42.52), p  = 0.001 Chordee Severity (n = 457)      None (0°) Referent Referent  Mild (1–29°) 3.41 (0.43-26.80), p = 0.24 3.90 (0.50-30.50), p = 0.20  Moderate (30–60°) 3.91 (0.48-31.66), p = 0.20 3.61 (0.45-29.01), p = 0.23  Severe (≥61°) 4.11 (0.50-34.02), p = 0.19 3.95 (0.48-32.51), p = 0.20 # of Stages of Repair      Single-stage Referent Referent  Multi-stage 1.97 (1.01-3.84), p  = 0.047 1.76 (0.89-3.47), p = 0.11 Pre-operative Testosterone      No Referent Referent  Yes 1.65 (0.92–2.98), p = 0.10 1.43 (0.78–2.62), p = 0.25 Meatal Mismatch      No mismatch – Referent  Meatal downstaging – 0.88 (0.25-3.01), p = 0.84  Meatal upstaging – 3.04 (1.34-6.88), p  = 0.007